Pengaruh Penggunaan Media Video Pembelajaran terhadap Hasil Belajar Biologi - Yendrita Yendrita; Yeza Syafitri (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2019)
This study aims to determine the effect of using video learning media on the biology learning outcomes of class X students at SMA Negeri 1 Situjuah Limo Nagari District. This research is a quasi-experimental research with a Posttest-Only Control Design research design. The population of this study was the X grade students of the 2016/2017 academic year, totaling 7 classes. The research sample of 2 classes was taken by purposivever sampling. Class X.5 as the experimental class and class X.6 as the control class. The research instrument used was a test. Data were analyzed by the t test, wherein the normality test and homogeneity test first. The results of the study, based on the final test scores of students' biology learning outcomes, obtained an experimental class average of 78.58 with a standard deviation of 10.18 and a control class of 71.44 with a standard deviation of 9.05. Based on data analysis, it is obtained thitung = 2.64> t table = 1.67, meaning that H0 is rejected and H1 is accepted. Thus it can be concluded that there is an influence of the use of video learning media on the learning outcomes of biology class students Keywords: learning videos, learning outcomes